First report of Cricocephalus albus (Digenea: Pronocephalidae) from Peru, parasite of the green turtle (Chelonia mydas agassizii) - Gomez-Puerta, Luis A. (2017)
Cricocephalus albus (Digenea: Pronocephalidae) is registered for first time in Peru in the East Pacific green turtle (Chelonia mydas agassizii). The parasites were collected during a necropsy carried out in a stranded sea turtle in the Virrilá estuary, located in the Sechura province of Piura, Peru. The specimens were studied morphologically and identified as C. albus. The current work describes C. albus, as well as the discussion of its hosts and geographic distribution.